Report on industrial attachment with Temasek Lab@NTU - Gui, Lin. (2010)
This report describes the research project on the Rapid Transform in my Industrial Attachment at Temasek Lab@NTU in Semester2 of Academic Year 2009. The Rapid Transform (RT) is well known by its fast translation invariant property, and popular used in simple pattern recognition, as it is fast in speed. The main purpose of this report is to introduce two new mathematical models of RT and to propose a new attempt in applying RT in motion estimation. Firstly, RT is better understood by using two proposed mathematical models. One is for RT under cyclic permutation which extends the input index to the whole integer region. The other is the model to express 2N points RT by using two N points RTs, which is important in mathematical induction. Secondly, it is the first time to use RT directly in fast motion estimation in H.264 codec. Some modifications in RT were also suggested to enhance performance.